Daily Pomegranate Intake Has No Impact on PSA Levels in Patients with Advanced Prostate Cancer - Results of a Phase IIb Randomized Controlled Trial - Stenner-Liewen, Frank (Ivyspring International Publisher, 2013)
Pomegranate has been shown to prolong PSA doubling time in early prostate cancer, but no data from a placebo controlled trial has been published yet. The objective of this study was to prospectively evaluate the impact of pomegranate juice in patients with prostate cancer. We conducted a phase IIb, double blinded, randomized placebo controlled trial in patients with histologically confirmed prostate cancer. Only patients with a PSA value ≥ 5ng/ml were included. The subjects consumed 500 ml of pomegranate juice or 500 ml of placebo beverage every day for a 4 week period. Thereafter, all patients received 250 ml of the pomegranate juice daily for another 4 weeks. PSA values were taken at baseline, day 14, 28 and on day 56. The primary endpoint was the detection of a significant difference in PSA serum levels between the groups after one month of treatment. Pain scores and adherence to intervention were recorded using patient diaries. 102 patients were enrolled. The majority of patients had castration resistant prostate cancer (68%). 98 received either pomegranate juice or placebo between October 2008 and May 2011. Adherence to protocol was good, with 94 patients (96%) completing the first period and 87 patients (89%) completing both periods. No grade 3 or higher toxicities occurred within the study. No differences were detected between the two groups with regard to PSA kinetics and pain scores. Consumption of pomegranate juice as an adjunct intervention in men with advanced prostate cancer does not result in significant PSA declines compared to placebo.